2013
DOI: 10.12705/622.12
|View full text |Cite
|
Sign up to set email alerts
|

Global legume diversity assessment: Concepts, key indicators, and strategies

Abstract: While many plant species are considered threatened under anthropogenic pressure, it remains uncertain how rapidly we are losing plant species diversity. To fill this gap, we propose a Global Legume Diversity Assessment (GLDA) as the first step of a global plant diversity assessment. Here we describe the concept of GLDA and its feasibility by reviewing relevant approaches and data availability. We conclude that Fabaceae is a good proxy for overall angiosperm diversity in many habitats and that much relevant dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 184 publications
0
64
1
7
Order By: Relevance
“…Legumes constitute a significant proportion of the canopy trees in tropical forests, especially in the Neotropics and Africa (Yahara et al 2013). Since energetic costs to support N fixing organisms (N 2 -fixing bacteria known as rhizobia) are large, N fixation cannot always be an advantageous strategy compared to investment of C resources to root growth (Crews 1999).…”
Section: Distribution Of Tropical Treesmentioning
confidence: 99%
“…Legumes constitute a significant proportion of the canopy trees in tropical forests, especially in the Neotropics and Africa (Yahara et al 2013). Since energetic costs to support N fixing organisms (N 2 -fixing bacteria known as rhizobia) are large, N fixation cannot always be an advantageous strategy compared to investment of C resources to root growth (Crews 1999).…”
Section: Distribution Of Tropical Treesmentioning
confidence: 99%
“…ectomycorrhizae) and bacteria (i.e. capturing soil nitrogen; see [12]); and (iii) produce edible fruits rich in proteins that can sustain wildlife, especially lemurs (see [28] and references therein). A recent study conducted in northeastern Madagascar showed that Leguminosae is the family that mostly contributes to the diet of lemurs in this area [29].…”
Section: (A) Legumes As a Proxy Of Plant Biodiversity And Ecosystem Smentioning
confidence: 99%
“…The legume family (Leguminosae; alternative name Fabaceae) is considered one of the largest, most economically significant plant families (Yahara et al 2013). It is the third largest angiosperm family with about 19,400 species (Lewis et al 2005) and its considerable importance in agriculture, its ability to occupy different habitats and diverse life forms are well documented (Yahara et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is the third largest angiosperm family with about 19,400 species (Lewis et al 2005) and its considerable importance in agriculture, its ability to occupy different habitats and diverse life forms are well documented (Yahara et al 2013). Projects such as the Global Legume Diversity Assessment are a first step in studying the rapid loss of legume species diversity.…”
Section: Introductionmentioning
confidence: 99%